The Impact of Google Apps at Work: Higher Educational Perspective - Al-Emran, Mostafa; Malik, Sohail Iqbal (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Google Apps brought many opportunities to enhance the work performance in the higher educational settings. This study aims to investigate the impact of Google Apps at work from the perspective of the higher educational institutions. An online questionnaire survey has been prepared and distributed among the academic and administrative staff at Al Buraimi University College, Oman for data collection. The total number of participants was 34. Different statistical analyses were performed on the collected data. Results revealed that the administrative staffs were more positive toward using Google Apps than the academics in performing their work while 58.8 % of the Academics indicated that they are using Google Apps in processing their work. The results of this study indicate that Google Apps are highly perceived by both academic and administrative staffs. This is evidence that these Apps have a significant impact on performing the work in the higher educational settings. Limitations and future work have been addressed.